2016
DOI: 10.1002/aic.15357
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐transfer enhancement in single drop extraction in the presence of magnetic nanoparticles and magnetic field

Abstract: Magnetite nanoparticles with an average particle size of 28.8 nm were synthesized, coated with oleic acid, and characterized using various techniques such as DLS, FT‐IR, SEM, XRD, VSM, and UV‐Vis analysis. A nanofluid consisting of synthesized nanoparticles and 5 wt % acetic acid in toluene as the dispersed phase was prepared and used in the chemical test system, Toluene‐Acetic Acid‐Water, for the single drop extraction in the presence and absence of an external oscillating magnetic field. Influences of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…They reported that increasing the magnetic nanoparticle concentration initially increased the mass transfer rate due to micro-convection, but the mass transfer rate began to decrease above a certain concentration due to the undesired agglomeration and aggregation of the magnetic nanoparticles. Increasing the magnetic field strength increased the mass transfer, whereas increasing the magnetic field frequency initially increased the mass transfer rate the improved momentum transfer caused by the Brownian motion, but then decreased due to the prevention of the nanoparticle movement inside the dispersed droplets at higher frequencies [57].…”
Section: Magnetic Nanoparticles Under a Magnetic Fieldmentioning
confidence: 98%
See 2 more Smart Citations
“…They reported that increasing the magnetic nanoparticle concentration initially increased the mass transfer rate due to micro-convection, but the mass transfer rate began to decrease above a certain concentration due to the undesired agglomeration and aggregation of the magnetic nanoparticles. Increasing the magnetic field strength increased the mass transfer, whereas increasing the magnetic field frequency initially increased the mass transfer rate the improved momentum transfer caused by the Brownian motion, but then decreased due to the prevention of the nanoparticle movement inside the dispersed droplets at higher frequencies [57].…”
Section: Magnetic Nanoparticles Under a Magnetic Fieldmentioning
confidence: 98%
“…Therefore, the addition of particular surfactants such as oleic acid is needed to stabilize nanoparticle suspension [57]. However, it should be noted that the addition of surfactants and stabilizing agents may influence the nanofluid mass transfer performance, and should be avoided when possible [58].…”
Section: Synthesis Of Nanoparticles and Preparation Of Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this process is also leukocyte-leukocyte interaction, which is L-selectin-dependent [4-6 same], when leukocyte roll over a layer of other leukocytes attached to the activated endothelial cells. L-selectin is also known to be related to some diseases like diabetes, sepsis, and meningitis [10][11][12][13][14][15]. L-selectins also guide lymphocytes to find lymph nodes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Application of novel techniques using various fluids on mass transfer rate and the use of nanoparticles in fluids was also proposed for enhancement of mass transfer process . H 2 S and CO 2 removal from biogas and the study of the presence of nanoparticles in water to enhance mass transfer in conventional techniques based on physical absorption has received more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%